2018
DOI: 10.1039/c8nh00123e
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature driven inter-valley carrier transfer and significant fluorescence enhancement in multilayer WS2

Abstract: A high-temperature driven carrier transfer process of multilayer WS2 is proposed and demonstrated for significant fluorescence emission enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…In addition to the multilayer WSe 2 system, we have confirmed that the model of thermally driven carrier redistribution is also applicable to the multilayer MoS 2 and multilayer WS 2 materials described in our previous studies . Similarly, the PL intensity increases by several times, even hundreds of times, at high temperatures compared to that achieved at room temperature.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…In addition to the multilayer WSe 2 system, we have confirmed that the model of thermally driven carrier redistribution is also applicable to the multilayer MoS 2 and multilayer WS 2 materials described in our previous studies . Similarly, the PL intensity increases by several times, even hundreds of times, at high temperatures compared to that achieved at room temperature.…”
supporting
confidence: 86%
“…Thus, heat engineering cannot only fulfill the modulation of the peak position but can also effectively transform the recombination channels of the indirect transition in multilayer WSe 2 . This phenomenon is different from other TMDs materials, which have fixed indirect transition pathways regardless of the changing temperature . This can be attributed to the transformation of an indirect bandgap from Λ–Γ to K–Γ as the temperature increases.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…Compared to their monolayer counterparts, few-layer TMDs have many notable superiorities such as higher electron mobility, stronger photon absorption ability and larger optical density of states. 47 For example, the few-layer WS 2 has been demonstrated to be an excellent channel material with good electron mobilities of 234 cm 2 V −1 s −1 and on/off ratios exceeding 10 8 for the making of high performance field-effect transistors, required for both energy saving and high power electronics applications. 48 In this present work, we report the use of femtosecond transient absorption spectroscopy to address separately the ultrafast nonequilibrium dynamics of electrons and holes in the formation process of the lowest X A at the K-valley in few-layer WS 2 , used as an example.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress has explored important physics related to the transition of excitons and trions, such as the valley lifetime of excitons (trions), spatial motion of excitons (trions), and spin and valley polarization dynamics of excitons (trions) . When excitons or trions transit from excited states to the ground state, excess energy will be dissipated by releasing photons in a process called fluorescence luminescence . The fluorescence lifetime is another parameter that describes the average time consumed during the excitons’ transition, playing a significant role in characterizing the exciton dynamics.…”
mentioning
confidence: 99%